Combination of Serum Amyloid A and C-Reactive Protein Exhibit Synergistic Effect in Angiogenesis by Inducing Inflammation and Vascular Network - Liu, Dan; Chen, Yonghe; Wang, Yunxiu; Lei, Mangjuan; Chen, Lin; Liang, Rongliang; Cheng, Zhaomin; Shi, Wen; Wang, Huimin; Lin, Li; Wang, Lina; Lin, Fujia; et al. (Frontiers in Oncology, 2020)
The role of angiogenesis in tumor progression has been recognized as one of hallmarks of cancer but the mechanism of its action remains unclear. Inflammatory markers serum amyloid A (SAA) and C-reactive protein (CRP) are proposed to play causal roles in the development of various disorders, including malignancies. Previously, we identified the complex of CRP and SAA (CRP-SAA) with diagnostic and prognostic value better than either one of them in the serum of lung cancer patients. In this study, we further explored the stimulation function of CRP-SAA on angiogenesis and inflammation. To explore possible mechanisms, microarray datasets were downloaded from the Gene Expression Omnibus (GEO) database and multi-bioinformatics analysis revealed that THP-1 and human umbilical vein endothelial cells (HUVECs) responded to SAA stimulation with upregulation of two pro-angiogenic cytokines in common, i.e., C-X-C motif ligand 6 (CXCL6) and CXCL8, which were validated by subsequent experiments in vitro. CRP had weak effects as a single stimulus, but it can efficiently potentiate the SAA induction of cytokines, which was stronger than the sum of the both (P<0.001). The synergistical effect of the combination of CRP and SAA enhanced HUVECs transwell and constricted morphology by up-regulating the pro-angiogenic genes. These results indicated that the binding of CRP and SAA acted synergistically in pro-angiogenesis by increasing inflammation and inducing vascular network.